Detection of toxic Microcystis spp. genotypes with diﬀerent environmental preferences. Case study: Salto Grande reservoir (INNOTEC, 2018)
In this work, the dynamics and toxicity of Microcystis spp. in Salto Grande reservoir (Uruguay river), as well as the genetic diversity of their toxic populations were assessed in winter and summer during 2013. Cell abundance of Microcystis spp. variated amongst diﬀerent sites and between seasons, showing a signifcantly higher cell and toxic genotype abundances (copies of mcyE gene) and microcystin-LR concentration during summer. Furthermore, when genetic diversity of toxic Microcystis was analyzed by high resolution melting analysis of mcyJ amplicons, two genotypes exhibiting diﬀerent environmental preferences were detected (cluster 1 and 2). Cluster 1 included samples found at water conditions of low temperature (lower than 17,6 °C) and slightly high conductivity (~52 to 58 µS cm-1), showing small Microcystis abundance and absence of microcystin-LR, whereas cluster 2 comprised samples from higher temperatures (between 17,6 and 25,9 °C) and lower conductivity (~50 to 52 µS cm-1) conditions, and with a higher cell abundance and microcystin-LR production. Our results suggest that toxic Microcystis spp. populations that bloom during summer are diﬀerent from those that persist during winter and pointed to water temperature and conductivity as relevant variables that control their abundance and toxicity.
Keywords: Microcystis; toxic genotypes; mcyJ; HRM; Salto Grande reservoir